Case Report: Short-Term Spinal Cord Stimulation and Peripheral Nerve Stimulation for the Treatment of Trigeminal Postherpetic Neuralgia in Elderly Patients - Zhao, Lin; Song, Tao (Frontiers in Neurology, 2021)
Objective: We aimed to report on the use of short-term high cervical spinal cord stimulation (SCS) combined with peripheral nerve stimulation (PNS) to successfully treat trigeminal postherpetic neuralgia (TPHN) affecting the V2 and V3 divisions. We also sought to use a novel PNS approach to the maxillary nerve next to the external opening of the foramen rotundum (FR) to treat TPHN at the V2 division. Method: Two elderly patients successfully treated with different neuromodulation methods for TPHN are presented in this case series. Results: The first case referred to an 83-year-old Chinese female patient with V2 and V3 TPHN who experienced a significant pain relief using a combination of short-term high cervical SCS at the C1–C2 level and PNS on the infraorbital nerve (ION). Case 2 was a 68-year-old Chinese male patient with V1 and V2 TPHN that obtained an excellent pain relief after having received short-term PNS on the supraorbital nerve (SON), the supratrochlear nerve (STN), and the maxillary nerve. Both reported improvements in their quality of life and ability to perform daily tasks during a 3-month follow-up period. Conclusions: Short-term high cervical SCS at the C1–C2 spinal segments may be a feasible method to treat recent-onset V3 TPHN in elderly patients. Additionally, by placing the stimulation lead next to the external FR opening, we demonstrated a novel PNS approach to the maxillary nerve not previously reported for TPHN therapy.